2015
DOI: 10.1155/2015/512027
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-Induced Cross Talk between PTEN and miRs 221/222 in Thyroid Cancer

Abstract: High mobility group box 1 (HMGB1) is an ubiquitous protein that plays different roles in the nucleus, cytoplasm, and extracellular space. It is an important DAMP molecule that allows communication between damaged or tumor cells and the immune system. Tumor cells exploit HMGB1's ability to activate intracellular pathways that lead to cell growth and migration. Papillary thyroid cancer is a well-differentiated tumor and is often used to study relationships between cells and the inflammatory microenvironment as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The role of the proinflammatory cytokine high-mobility group box 1 protein (HMGB1) in GD has not yet been defined, but a recent study showed that HMGB1 increases miRNA 221 and 222 expression in the papillary cancer cell line BCPAP as well as in excised papillary lesions 37. Because HMGB1 has been associated with cell invasion and metastasis through NF-κB and MAPK signalling,37 38 among other pathways, its role in the pathogenesis of GD and PTC must be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the proinflammatory cytokine high-mobility group box 1 protein (HMGB1) in GD has not yet been defined, but a recent study showed that HMGB1 increases miRNA 221 and 222 expression in the papillary cancer cell line BCPAP as well as in excised papillary lesions 37. Because HMGB1 has been associated with cell invasion and metastasis through NF-κB and MAPK signalling,37 38 among other pathways, its role in the pathogenesis of GD and PTC must be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…e abnormal high expression of miR-221/222 is involved in various cancers (Table 1), which promotes the malignant proliferation, immune escape, invasion, and metastasis of tumor cells [94]. rough the retrieval and statistics of the databases (including PubMed and Web of Science), the oncogene upregulated with overexpression of miR-221/222, including glioblastoma [31], gastric cancer [32,33], bladder cancer [35], hepatocellular carcinoma [38,39,51,59], lung cancer [36,37], liver cancer [29,51], breast cancer [60][61][62][63], cervical cancer [64,68,95], ovarian cancer [66,69,70], endometrial carcinoma [74], melanoma [75,76], pancreatic cancer [77], thyroid cancer [78,79], multiple myeloma [80], chronic lymphocytic leukemia [79], oral carcinoma [82], retinoblastoma [83,96], nasopharyngeal carcinoma [84], and prostate carcinoma [85], was summarized. However, the upregulation of miR-221/222, also referred to as tumor suppressor miRNA, targeting overexpress oncogenes, leads to tumor suppressions.…”
Section: Mir-221/222's Targets and Molecular Modulationmentioning
confidence: 99%
“…An abundance of preclinical data and retrospective analyses support research to develop methods to accentuate ICD for clinical therapies, especially using protocols that are compatible with current standards of care (Garg & Agostinis 2016). ICD has been underexplored in thyroid cancers; current studies are limited to evaluating hallmark damageassociated molecular patterns as prognostic markers or drivers of disease (Netea-Maier et al 2008, Mardente et al 2015, Guan et al 2017. BRAF V600E mutations in papillary thyroid cancers appears to downregulate the expression of HMGB1, adding further evidence to suggest this mutation is immunosuppressive in nature (Guan et al 2017).…”
Section: :12mentioning
confidence: 99%